Lactate Contribution to the Tumor Microenvironment: Mechanisms, Effects on Immune Cells and Therapeutic Relevance - Romero-Garcia, Susana; Moreno-Altamirano, María Maximina B.; Prado-Garcia, Heriberto; Sánchez-García, Francisco Javier (Frontiers in Immunology, 2016)
Malignant transformation of cells leads to enhanced glucose uptake and the conversion of a larger fraction of pyruvate into lactate, even under normoxic conditions; this phenomenon of aerobic glycolysis is largely known as the Warburg effect. This metabolic reprogramming serves to generate biosynthetic precursors, thus facilitating the survival of rapidly proliferating malignant cells. Extracellular lactate directs the metabolic reprogramming of tumor cells, thereby serving as an additional selective pressure. Besides tumor cells, stromal cells are another source of lactate production in the tumor microenvironment, whose role in both tumor growth and the anti-tumor immune response is the subject of intense research. In this review, we provide an integral perspective of the relationship between lactate and the overall tumor microenvironment, from lactate structure to metabolic pathways for its synthesis, receptors, signaling pathways, lactate-producing cells, lactate-responding cells, and how all contribute to the tumor outcome. We discuss the role of lactate as a immunosuppressor molecule that contributes to tumor evasion and explore the possibility of targeting lactate metabolism for cancer treatment, as well as of using lactate as a prognostic biomarker.